Dadiangas General Hospital a strategic plan for 2007-2011 - Acuña, Thaddeus R. (School of Management, University of the Philippines Mindanao, 2007)
The Dadiangas General Hospital (DGH) has been in business operation for the past four decades. It started in 1962 as the first privately owned hospital in General Santos City. Today, it has grown into one of the most formidable hospital in the city with 145 bed capacity and an increasing occupancy rate in the past five years from 71.5% in 2002 to 98.05 in 2005. Annual revenues also increase from P93.9 M in 2001 to 150.3 M in 2005, which is translated into an annual average growth rate of 12.8% over the last five years. Yet, in spite of these positive growths, the company acknowledges that it has still to attain full growth potential. Accordingly, this could be attributed to the absence of strategic planning which is a very common characteristic of a typical family-owned business. Over the years, the growth of DGH is heavily dependent on its strategic location being located in the heart of the city and its well-established reputation for being the first privately-owned hospital in the city. It is on this premise that tis strategic plan is formulated to introduce to management a more systematic approach to planning and to formulate strategic interventions that will address the issues and concerns besetting DGH. The strategic plan will take advantage of the distinct strengths and comparative advantages of DGH to further enhance its competitiveness and sustain its growth in the next five years. The conceptual framework adopted in the formulation of the strategic plan is based on the Comprehensive Model of the Strategic Management Process by Fred R. David (2005). This framework presents a clear and practical approach in formulating, implementing and evaluating strategies which are applicable to the operation of DGH. This framework provides the road map for the formulation of the strategic plan for DGH. Chapter 1 of this paper presents the overview of the corporate history and general performance of DGH over the past five years. It provides a common understanding of DGH being a private business entity. Chapter 2 shows an overview of the hospital industry in the Philippines, which is further deduced, where applicable, to the specific geographic market of DGH. External factors affecting the industry are processed with the used of Porter?s five forces model of competitiveness. The presence of several hospitals in the South Cotabato, Sultan Kudarat, Sarangani and General Santos City (SOCSKSAREN) intensifies rivalry between and among similarly classified hospitals operating in the area. Further analysis of external factors reveals the vast opportunities for growth as well as the threats to the industry. Chapter 3 outlines a detailed review of the internal environment of DGH. It reveals the competitive edge of the institution which basically lies on its strategic location and reputation for delivering quality healthcare services to its clienteles. The application of the total quality management and continuous improvement approaches provides DGH competitive edge over its competitors. This is particularly espoused in its readiness to implement the Benchbook, a framework for quality assurance, which is a mandatory requirement imposed by the Philippine Health Insurance Corporation (PHIC). The review and reformulation of the vision, mission goal (VMG) and objectives of DGH are discussed in Chapter 4. A participatory workshop, attended by key officers and personnel, was conducted to come up with a comprehensive and well-thought vision, mission, goal and objectives for the company. The new vision of becoming a one-stop-shop hospital now serves as the direction for which the corporate goal is directly focused on. The corporate goal aims to become a self-sustaining 250 bed capacity hospital by 2016. This will be pursued in two developmental phases covering five year period for each phase. Phase 1 covers the first five years (2007-2011) and is the main coverage of this strategic plan. The major target under Phase 1 is to double total revenues and total bed capacity of DGH within the period. An integrated strategy is formulated based on the results of the analysis on the key external and internal factors affecting the competitiveness of DGH. This strategy is anchored on the mandatory compliance to the Benchbook program and the integration of the marketing and financial components into this program. The process of coming up with this strategic choice is presented in detail in Chapter 5. On the other hand, the covering implementing programs for this integrated strategy are discussed in Chapter 6. This chapter also presents the financial projections in order to provide quantitative measures on the financial impact of implementing the integrated strategy. Finally, Chapter 7 presents the key control mechanisms. This is generally guided by the formulation of the key results area (KRA) matrix as the primary tool for control. The KRA matrix facilitates a systematic monitoring, review and evaluation of the actual performance and accomplishments vis-à-vis the desired deliverables and outputs from the implementation of the integrated strategy.